2015
DOI: 10.1017/s003060531500037x
|View full text |Cite
|
Sign up to set email alerts
|

Continuing mortality of vultures in India associated with illegal veterinary use of diclofenac and a potential threat from nimesulide

Abstract: The collapse of South Asia's Gyps vulture populations is attributable to the veterinary use of the non-steroidal anti-inflammatory drug (NSAID) diclofenac. Vultures died after feeding on carcasses of recently-medicated animals. The governments of India, Nepal and Pakistan banned the veterinary use of diclofenac in 2006. We analysed results of 62 necropsies and 48 NSAID assays of liver and/or kidney for vultures of five species found dead in India between 2000 and 2012. Visceral gout and diclofenac were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 27 publications
4
60
0
Order By: Relevance
“…) and nimesulide (Cuthbert et al . ). It has been suggested that NSAIDs that are nephrotoxic to a particular bird species are those with long elimination times from the plasma in that species (Hutchinson et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and nimesulide (Cuthbert et al . ). It has been suggested that NSAIDs that are nephrotoxic to a particular bird species are those with long elimination times from the plasma in that species (Hutchinson et al .…”
Section: Introductionmentioning
confidence: 97%
“…There is also circumstantial evidence of nephrotoxicity of diclofenac to the steppe eagle Aquila nipalensis (Sharma et al 2014). Hence, it is possible that obligate and facultative scavenging birds other than Gyps vultures are affected by diclofenac as well as by other nephrotoxic NSAIDs, such as ketoprofen (Naidoo et al 2010) and possibly also by flunixin (Zorrilla et al 2015) and nimesulide (Cuthbert et al 2016). It has been suggested that NSAIDs that are nephrotoxic to a particular bird species are those with long elimination times from the plasma in that species (Hutchinson et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The safety of meloxicam has since been demonstrated in the G. bengalensis, G. indicus and G. coprotheres (Swan et al 2006a). As a result of the advocacy on the use of meloxicam and the concurrent ban on the sale of diclofenac for veterinary use, the previous rate of decline has been slowed with the population finally showing a small degree of recovery (Cuthbert et al 2011, Cuthbert et al 2016. For example in Pakistan, there was an increase vulture nesting sites from 11 observed during a survey conducted between 2010-2011 to 34 between 2011-2014 (Murn et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, experimental safety testing shows that one is vulture‐toxic (ketoprofen) (Naidoo et al , ) and another is vulture‐safe (meloxicam) (Swan et al ; Swarup et al ). Two others are almost certainly toxic given that elevated residues of these drugs have been found in dead vultures with clinical signs of NSAID poisoning (flunixin [Zorrilla et al 2014] and nimesulide [Cuthbert et al ]).…”
Section: Introductionmentioning
confidence: 99%